5' and 3' splicing signals evolution in vertebrates: Analysis in a conserved gene family. (June 2020) - Panaro, Maria A.; Calvello, Rosa; Mitolo, Vincenzo; Cianciulli, Antonia
Graphical abstract: Highlights: In this analysis of the zebrafish, chicken, mouse, and human homologous SLC25 gene introns we describe the conservation/mutation dynamics of the zebrafish 5'ss and 3'ss in the evolution to birds and mammals. Mitochondrial solute carrier genes of zebrafish, chicken, mouse, and human, the introns are located at exactly superimposable positions. As a result of evolutionary dynamics, the general nucleotide composition at each position has remained remarkably conserved throughout vertebrates. Conservation loss is higher in the evolution from fish to the last common ancestor of birds and mammals and diminishes in the successive evolution steps up to the mammalian common ancestor, and becomes still lower at the divergence of rodents and primates. The family of the SLC25 homologous genes presents aspects of an overall long-term evolutionary exon/intron architecture stability, which contrasts with the wide-range variability of the intron-ends signals. Abstract: The mitochondrial solute carrier genes (SLC25) are highly conserved during vertebrate evolution. In most SLC25 genes of zebrafish, chicken, mouse, and human, the introns are located at exactly superimposable positions. In these topographically corresponding introns we studied the composition of the initial and terminal hexanucleotides (5'ss and 3'ss) which are instrumental in splicing signaling, focusing on the evolutionary conservation/mutation dynamics of these genetically related sequences. At each position, the per cent conservation of zebrafish individual nucleotides in chicken, mouse and human is proportional to their percent frequency in zebrafish; furthermore, nucleotide mutations are biased in favor of the more represented nucleotides, thus compensating for those highly represented zebrafish nucleotides which have not been conserved. As a result of these evolutionary dynamics, the general nucleotide composition at each position has remained relatively conserved throughout vertebrates. At 5'ss, following the canonical GT, A and G are largely prevailing at position +3, A at +4 and G at +5 (GT[A/G]AGx). At 3'ss, T and C are largely prevailing at positions −6, −5 and −3, preceding the canonical intron terminal AG ([C/T] [C/T]x[C/T]AG). However, the actual composition of the tetranucleotides at 5' and 3' often does not conform to the above scheme. At 5'ss the more canonical sequence is completely expressed in 63% of cases and partially (2 or 1 matches) in 37 % of cases. At 3'ss the more canonical sequence is completely expressed in 71 % of cases and partially (2 or 1 matches) in 29 % of cases. The nucleotide conservation loss (nucleotide mutation) is higher in the evolution from fish to the last common ancestor of birds and mammals (58 %), then diminishes in the successive evolution steps up to the mammalian common ancestor (10 %), and becomes still lower at the divergence of rodents and primates (5 %).